(untitled) - Khosrowpour, Mehdi (Hershey P.A., 2006)
For students and professionals, this collection of 15 case studies discusses the successful use of database technologies, database research, systems analysis and design, and the utilization of software engineering technologies in database applications and management. Cases describe a library database, data warehouses, non-profit organizations, the use of a geographic information system, information technology and law enforcement, online course management systems at universities, document management, data mining, Conceptual Schema, and IT architecture at a real estate firm. Khosrow-Pour, the editor-in-chief of Journal of Cases on Information Technology is executive director of the Information Resources Management Association, has taught courses on information systems, and has written about 30 books on information technology management.
Keywords: Information technology,Database management; Management